The Influence of Employee Empowerment and Compensation on Employee Performance at PT BPR Majalengka Jabar - Asep Arifani Siswanto; Sudibyo Budi Utomo; Eli Dahlia; Tuti Yuliawati (Politeknik Mardira Indonesia, 2025)
The Influence of Employee Empowerment and Compensation on Employee Performance PT BPR Majalengka West Java Employee performance improvement can be achieved in various ways, one of which is by providing employee empowerment and providing compensation that is in accordance with employee expectations. The purpose of this study is to determine the effect of employee empowerment and compensation on employee performance. The method used in the analysis is descriptive and verification. A sample of 68 respondents was taken usingsaturation sampling technique. Statistical testing using multiple regression analysis, coefficient of determination and to test the hypothesis using the t-test and F-test using the help of SPSS 25 for Windows software. The conclusion that the author can convey after conducting research and discussion regarding the influenceemployee empowerment andcompensationon employee performance, it can be concluded as follows:The closeness of the relationship between the independent variable and the dependent variable simultaneously is indicated by the value R = 0.879This figure shows a very strong relationship between all independent variables X and dependent variable Y. Through the results of data processing, a variable prediction model can be formed.employee empowerment andcompensationon employee performanceas follows: Y = 0.050 + 0.179X1+ 1.060X2. The results of data processing show that the R2 value is 0.881or 88.1%, this shows that the contributionemployee empowerment andcompensation for the increase or decrease in employee performance is 88.1% and the remaining 11.9% is a contribution from other variables that are not included in the model proposed in the study. Based on the hypothesis test, it shows that the Fcount value = 240.225, where the Ftable value =3.14So it is proven that there is a significant influence betweenemployee empowerment andcompensation for employee performance. So H0 is rejected and H1 is accepted because Fcount (240.225) > Ftable (3.14)).